A review on carbon nanotubes and graphene as fillers in reinforced polymer nanocomposites - Mittal, Garima; Dhand, Vivek; Rhee, Kyong Yop; Park, Soo-Jin; Lee, Wi Ro (Journal of industrial and engineering chemistry (Seoul, Korea), 2015)
Recently, carbonaceous nanofillers such as graphene and carbon nanotubes (CNTs) play a promising role due to their better structural, functional properties and broad range of applications in every field. This paper reviews the synthesis and properties of CNTs along with the use of graphene as a novel substitution to the nanotubes as fillers. This review also focuses on the issues related to the processing, dispersion and alignment of CNT within nanocomposites. Furthermore a comparative analysis has been carried out between the importance of graphene and carbon nanotubes as fillers and their substantial changes in mechanical and electrical properties of matrix.